2015
DOI: 10.1093/eurpub/ckv215
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic environment, area facilities and obesity and physical inactivity among children

Abstract: In the city of Madrid, socio-economic context of neighbourhood of residence shows an inverse relationship with obesity but not with physical inactivity among children. The relationship observed with obesity is not explained by the availability of area facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Regarding the socioeconomic gradient, the Soltero et al study also found differences in all three cities by education and poverty levels. In Madrid, a recent study showed that youth living in more disadvantaged areas had greater odds of being obese compared with those living in more advantaged areas [64]. Yet, to date, there is no research for Southern European cities like Madrid, assessing whether these social disparities in obesity are associated with the food environment surrounding children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the socioeconomic gradient, the Soltero et al study also found differences in all three cities by education and poverty levels. In Madrid, a recent study showed that youth living in more disadvantaged areas had greater odds of being obese compared with those living in more advantaged areas [64]. Yet, to date, there is no research for Southern European cities like Madrid, assessing whether these social disparities in obesity are associated with the food environment surrounding children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…In low-income countries, children in the poorest households have been more affected by under-nutrition as they are exposed to suboptimal living conditions like poor sanitation while their better-off counterparts may have better living conditions but suffer from being overweight/obesity [8,[10][11][12][13]. However, in many settings, there is evidence that the burden of obesity is shifting towards the more vulnerable populations as inexpensive high-energy-dense and ultra-processed foods are becoming more available, affordable, convenient and therefore more readily consumed [1,[14][15][16][17]. These transitions are particularly pronounced in urban settings.…”
Section: Introductionmentioning
confidence: 99%
“…In most transitional countries, significant deviations from recommendations for healthy lifestyle was noted in childrens' habits, knowledge and practice [12][13][14] . Furthermore, a change in diet and sedentary lifestyle has been reflected in an increase of the number of overweight and obese children 15 . Measuring and assessing physical activity in childhood and the period of adolescence are important for the regulation of body weight, and they give important information on health potential as well.…”
Section: Introductionmentioning
confidence: 99%